LYMPHANGIOMA OF TONGUE - Bajpai, Manas; Pardhe, Nilesh (Journal of Ayub Medical College Abbottabad, 2018)
A 12-year-old girl reported to our institution for the evaluation of an asymptomatic swelling on her tongue since birth. The swelling was painless although patient complained of difficulty in mastication and speech. No history of pus discharge and bleeding was associated with the lesion. Intra - oral examination revealed multiple popular lesions on the right side of her dorsum surface of tongue few papules were blood filled and few lesions had the same colour as normal mucosa. (Figure-1) On palpation the lesions were soft, non-tender and pebbly. Based on clinical features a preliminary diagnosis of lymphangioma was considered. An incisional biopsy was done and the tissue was subjected to processing and staining by haematoxylin and eosin stains. Histopathological evaluation of the tissue revealed numerous dilated lymphatic channels which were lined by single layer of endothelial cells with flattened to ovoid nuclei, filled by lymph and occasional inflammatory cells. (Figure-2) These dilated vessels were located just beneath the epithelium with no or little intervening connective tissue stroma separating it from overlying epithelium. Connective tissue stroma was fibro-cellular and showed focal areas of lymph collection (The overlying epithelium was parakeratinized stratified squamous epithelium. (Figure-3) Based on microscopical features, the diagnosis of lymphangioma was rendered. Lymphangiomas were first described by Virchow in 1854 as rare, benign, congenital malformation of unknown cause originates from lymph vessels.1 Lymphangiomas are considered to arise from sequestration of lymph sac and enlarge due to improper drainage, due to the lack of communication with the central lymphatic channels or because of the excessive secretion of lining cells.2 They are most commonly present at birth, and might go unnoticed until after dentition erupts or even after puberty. However, few cases have been reported in adults also.3 Histopathologically they can be classified in 4 different patterns.3,4